2017
DOI: 10.1080/02786826.2017.1330535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanosilica (SiO2) and nanoalumina (Al2O3) reinforced polyester nanocomposites on aerosol nanoparticle emissions into the environment during automated drilling

Abstract: The aim of this study is to investigate the effect nanosilica and nanoalumina has on nanoparticle release from industrial nanocomposites due to drilling for hazard reduction whilst simultaneously obtaining the necessary mechanical performance. This study is therefore specifically designed such that all background noise is eliminated in the measurements range of 0.01 particles/cm 3 and §10% at 10 6 particles/cm 3. The impact nano-sized SiO 2 and Al 2 O 3 reinforced polyester has on nanoparticle aerosols generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…This would suggest the more holes being drilled also increases the particle number concentration peak size. Therefore, GO at 0.5 wt.% shows an increasing trend with more holes drilled, which is not evident within other studies [28][29][30].…”
Section: Filler Effect On Particle Number Concentrationcontrasting
confidence: 78%
See 2 more Smart Citations
“…This would suggest the more holes being drilled also increases the particle number concentration peak size. Therefore, GO at 0.5 wt.% shows an increasing trend with more holes drilled, which is not evident within other studies [28][29][30].…”
Section: Filler Effect On Particle Number Concentrationcontrasting
confidence: 78%
“…As discussed, currently only nine studies have evaluated the influence of nanoparticles on nanoparticle release during drilling [23][24][25][26][27][28][29][30][31]. All of the studies observed nanoparticle release and highlighted the potential hazard and exposure to humans which needs to be understood.…”
Section: Influence Of Fillermentioning
confidence: 99%
See 1 more Smart Citation